2002
DOI: 10.1093/emboj/21.9.2159
|View full text |Cite
|
Sign up to set email alerts
|

JAK2, complemented by a second signal from c-kit or flt-3, triggers extensive self-renewal of primary multipotential hemopoietic cells

Abstract: De®ning signals that can support the self-renewal of multipotential hemopoietic progenitor cells (MHPCs) is pertinent to understanding leukemogenesis and may be relevant to developing stem cell-based therapies.Here we de®ne a set of signals, JAK2 plus either c-kit or¯t-3, which together can support extensive MHPC self-renewal. Phenotypically and functionally distinct populations of MHPCs were obtained, depending on which receptor tyrosine kinase, c-kit or¯t-3, was activated. Self-renewal was abrogated in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 50 publications
(77 reference statements)
0
35
0
2
Order By: Relevance
“…25,44,45 Recent findings indicate that both Tpo signaling (via JAK2) and SF signaling are required for in vitro self-renewal of multipotent hematopoietic cells. 46 However, expansion of long-term repopulating cells can be achieved in H2K-BCL-2 transgenic bone marrow cells with a single growth factor (SF), indicating that one of the in vitro requirements is inhibition of HSC apoptosis. 47 Possible mechanisms for the Tpo-mediated regulation of HSCs have recently been unveiled, including inhibition of apoptosis via p53 48 and activation of self-renewal via HoxB4.…”
Section: Discussionmentioning
confidence: 99%
“…25,44,45 Recent findings indicate that both Tpo signaling (via JAK2) and SF signaling are required for in vitro self-renewal of multipotent hematopoietic cells. 46 However, expansion of long-term repopulating cells can be achieved in H2K-BCL-2 transgenic bone marrow cells with a single growth factor (SF), indicating that one of the in vitro requirements is inhibition of HSC apoptosis. 47 Possible mechanisms for the Tpo-mediated regulation of HSCs have recently been unveiled, including inhibition of apoptosis via p53 48 and activation of self-renewal via HoxB4.…”
Section: Discussionmentioning
confidence: 99%
“…This signaling pathway, through Akt, has been shown to play a crucial role in cytokine-mediated survival (31,46), as well as in the self-renewal of primary multipotential hematopoietic progenitors (47). Blockade of PI 3-kinase completely abolished the maintenance of hematopoietic progenitors mediated by VEGFR-2, indicating that this pathway is critical for VEGFR-2-mediated survival in bone marrow progenitor cells.…”
Section: Vegfr-2 Signaling In Hematopoietic Progenitorsmentioning
confidence: 99%
“…In contrast, other hematopoietic cytokine receptors, such as Mpl, induce a dramatic expansion of multipotential progenitors and megakaryocytes (21,23). A recent study has demonstrated that a combination of signals, JAK2 plus either c-Kit or Flt-3 together, can support extensive hematopoietic progenitor cell self-renewal although neither of these receptors can sustain the growth of bone marrow cells alone (47). Whether VEGFR-2 requires additional signals to induce cell proliferation in hematopoietic cells remains unknown, and further studies would be needed to assess this issue.…”
Section: Vegfr-2 Signaling In Hematopoietic Progenitorsmentioning
confidence: 99%
“…36 Unsurprisingly, this physiologic elegance has been difficult to exploit therapeutically. [37][38][39][40] A focus on receptors and other signaling molecules, 17,41 rather than ligands, might address many of these issues. In contrast to the promiscuity of ligands that can activate multiple receptors, or receptors expressed by multiple tissues, CIDs can activate specific receptors in specific tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Further insight into the basis for these differences, and their relationship to relative levels of transgene expression ( Figure 1G) will come from a direct prospective comparison between F36VMpl and F36VFGFR1 in highly purified ltHSCs, stHSCs, and various subsets of lineage-committed progenitors. 2 F36VFGFR1 joins F36VMpl [10][11][12][13][14][15][16] and a conditional derivative of Jak2 (VЈVJak2) 17,41 as the third CID-regulated "proliferation switch" with in vivo hematopoietic activity identified to date. With the caveat that direct comparisons of these signaling proteins are limited, and that the hematologic responses may depend on the duration of CID treatment, these signaling proteins appear to possess a progressively additive range of activities (Table 2), ranking from VЈVJak2 to For personal use only.…”
Section: Discussionmentioning
confidence: 99%